2013
DOI: 10.1186/1476-072x-12-23
|View full text |Cite
|
Sign up to set email alerts
|

A case-referent study: light at night and breast cancer risk in Georgia

Abstract: BackgroundLiterature has identified detrimental health effects from the indiscriminate use of artificial nighttime light. We examined the co-distribution of light at night (LAN) and breast cancer (BC) incidence in Georgia, with the goal to contribute to the accumulating evidence that exposure to LAN increases risk of BC.MethodsUsing Georgia Comprehensive Cancer Registry data (2000–2007), we conducted a case-referent study among 34,053 BC cases and 14,458 lung cancer referents. Individuals with lung cancer were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 41 publications
5
67
0
Order By: Relevance
“…In the past decade, several epidemiological studies have investigated the co-distribution between breast cancer incidence and light pollution [19][20][21][22]. These studies and others find compelling evidence supporting a potential role of electric light at night on breast cancer risk.…”
Section: Artificial Light At Night As a Risk Factor For Breast Cancermentioning
confidence: 99%
“…In the past decade, several epidemiological studies have investigated the co-distribution between breast cancer incidence and light pollution [19][20][21][22]. These studies and others find compelling evidence supporting a potential role of electric light at night on breast cancer risk.…”
Section: Artificial Light At Night As a Risk Factor For Breast Cancermentioning
confidence: 99%
“…The effects were not linked to a particular lighting technology but due directly or indirectly to artificial nighttime light itself. Studies have variously documented geographic and chronological covariance between patterns of nighttime lighting and the incidence of breast cancer and obesity (Kloog et al 2010;Wyse et al 2011;Bauer et al 2013). In the case of obesity, researchers concluded that chronic circadian desynchrony, defined as small daily changes in the 24 h light:dark cycle as induced by electric lighting, are associated with increasing weight gain and metabolic disorders such as diabetes in both experimental animals and in shift workers (Wyse et al 2011).…”
Section: Human Health and Wellbeingmentioning
confidence: 99%
“…The National Geophysical Data Center (NGDC) of the US National Oceanic and Atmospheric Administration (NOAA) provides time-series DMSP OLS images (Elvidge et al 2007). DMSP OLS imagery has been used in a wide variety of study areas such as urbanization (Lo 2002), population and socioeconomic estimation (Welch 1980;Sutton et al 2001;Doll, Muller, and Morley 2006;Gallaway, Olsen, and Mitchell 2010), and human health (Kloog et al 2008(Kloog et al , 2010Bauer et al 2013).…”
Section: Materials and Methods Datamentioning
confidence: 99%